Feticide, the conflict between Passion and Morals in William Faulkner’s the Wild Palms - Yadav, Dr. Jyoti (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
In "Foeticide, the conflict between Passion and Morals in William Faulkner’s The Wild Palms, I am trying to explore the historically persistent and socially significant theme of abortion. Faulkner depicts the male protagonist’s fear of female fertility and tackles the issue of abortion as a matter of individual choice with the withering of romantic love, wretched poverty, and maternal death corresponding with the popular discourse of a mid-twentieth-century U.S. that depicted abortion as tragic. Keywords : Foeticide, illicit love, failed marriage, death, imprisonment.